The effects of autologous platelet concentrate on the healing of intra-bony defects: a randomized clinical trial - Kudyar, Nitin; Dani, Nitin; Abullais, Shahab Saquib; AlQahtani, Nabeeh A.; Gupta, Aashima; Attar, Nilofar (European Oral Research, 2019)
The present study aimed to evaluate the clinical and radiographic effects of autologous platelet concentrate (APC) on the healing of intra-bony defects filled with β-tricalcium phosphate (β-TCP) and covered with collagen membranes. This study included 30 defects of 14 systemically healthy subjects. All of them had, at least, two deep intra-bony, inter-proximal periodontal defects. Minimum probing pocket depth (PPD) was 6 mm. Clinical and imaging examination was performed both at baseline and at 3, 6, and 9 months after surgery. Both the test and control group revealed a significant reduction in all variables when compared with the base line. Mean reduction of the PPD in two groups at each follow-up time point showed no significant difference. Means of the clinical attachment gain of the same groups were significantly different (p<0.05). Mean gingival recession at 3 month was not significant. However, the means of gingival recession coverage of two groups were significantly different at 6 and 9 months (p<0.05 for both). Sites treated with APC are more likely to demonstrate more clinical attachment gain and recession coverage at the end of 9 month compared to those without APC.